Time-resolved photoluminescence study of low-energy emission mechanisms in oligofluorene and polyfluorene films - Kang, Jihoon; Jo, Jungho; Jo, Youngeun; Lee, Sun Young; Keivanidis, Panagiotis E.; Wegner, Gerhard; Yoon, Do Y. (My University, 2008)
We report time-resolved photoluminescence (PL) spectroscopy study of solutions and thin films of pure penta-fluorenes with varying alkyl side-chain structures. While no low-energy green emissions were observed in solutions, spin-cast and vacuum dried initial films exhibited low-energy emission in time-delayed PL spectra, centered at 490 nm, whose intensity varied strongly with the side-chain structure. In comparison, the films annealed at 170 °C in air showed nearly identical low-energy emission in time-delayed PL spectra, centered at 520 nm, regardless of the side-chain structures. Therefore, our experimental results obtained for pure penta-fluorenes provided clear evidence that the mechanism of the green emission of oligofluorene and polyfluorene films includes both the intermolecular aggregate/excimer formation, emitted around 490 nm, and fluorenone-type chemical defects, emitted around 520 nm. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Polyfluorene; Oligofluorene; Time-resolved photoluminescence